2014
DOI: 10.3109/09638288.2014.923525
|View full text |Cite
|
Sign up to set email alerts
|

Ankle fractures and employment: a life-changing event for patients

Abstract: Ankle fracture patients are likely to suffer high rates of unemployment or disability shortly after their injury. Further investigations with a larger-scale, randomized patient population can provide important information on employment status following ankle fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…They suggested that improving patient compliance with attendance for rehabilitation may improve employment outcomes. 23 Ponzer et al in 1999 studied 53 patients with type B ankle fracture who were treated operatively. They found that about 60 percent of the patients had an excellent OMA score and a good clinical outcome.…”
Section: Inferencementioning
confidence: 99%
“…They suggested that improving patient compliance with attendance for rehabilitation may improve employment outcomes. 23 Ponzer et al in 1999 studied 53 patients with type B ankle fracture who were treated operatively. They found that about 60 percent of the patients had an excellent OMA score and a good clinical outcome.…”
Section: Inferencementioning
confidence: 99%
“…Unstable syndesmotic injuries occur in up to every seventh ankle fracture [1]. The high socioeconomic relevance of this injury has already been proven in the context of retrospective studies [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Trauma leading to fractures of the distal radius (DRF) or ankle (AF) is quite common, with incidence rates of 26–32 per 10 4 person years for DRF [ 1 3 ] and 10.1 per 10 4 person years regarding AF [ 4 ]. Patients may experience secondary fracture displacement [ 5 7 ], suffer from pain, stiffness, sleep difficulties, reduced grip strength, and/or restricted range of motion [ 8 12 ], which affect employment [ 13 15 ], sports [ 8 , 9 ], and quality of life (QOL; i.e., patients’ subjective evaluations of their functioning and well-being [ 16 – 18 ]).…”
Section: Introductionmentioning
confidence: 99%